ADVANCING EDUCATION SUSTAINABLE GROWTH IN NATIONAL TRAINER DEVELOPMENT - Ghifari, Muhammad (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
In this study, the researchers wanted to discuss how sustainable improvements were made by guardians in the development of the nursery. Researchers use a qualitative method that aims to explain the truth of a phenomenon that has the aim of obtaining objective data. Based on the results of the research, it can be concluded that in carrying out continuous improvement with the guardian in the development of the foster care there are several steps that have been applied among them: (a) to know closer with the centurion, to engage in close proximity with the clergyman as a guardian requires challenges that must be overcome on its own. Understanding the unique personality of each centri is pleasant when we are able to communicate with the heart. (b) Loving the mother-in-law, the guardian must provide emotional support as a key aspect. Listening attentively to their stories, their excitement, or their concerns is a first step in building a strong bond. One of the things to pay attention to is the fulfilment of basic needs, such as food, shelter, and clothing. The guardian should also ensure that the guardian has adequate access to educational facilities and learning facilities. (d) the prayer of the clergyman, the guardian is not only limited to the physical and educational aspects, but also includes attention to the spiritual dimension of the centurion